Edades Victorio C. Edades and modernism in Philippine art - Deocampo, Nick. ([s.l.] Center for New Cinema, 2004)
Recognized as the father of Philippine Modernism, Victorio C. Edades came of age during the American occupation of the Philippines, becoming one of the formative influences among local artists who struggled to define the nation's soul against its colonial past and present.
Director/Scriptwriter Nick Deocampo, producers: Committee on Galleries, National Commission for Culture and the Arts, cinematographer: Yam Laranas, Editor: Nonoy Dadivas.
All levels MTRCB rating: General Patronage.
Keywords: Edades, Victorio C. -- 1895-.; Art, Philippine; Modernism (Art)